2021
DOI: 10.1371/journal.ppat.1009496
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection restricts human LINE-1 retrotransposition in hepatoma cells

Abstract: LINE-1 (L1) retrotransposons are autonomous transposable elements that can affect gene expression and genome integrity. Potential consequences of exogenous viral infections for L1 activity have not been studied to date. Here, we report that hepatitis C virus (HCV) infection causes a significant increase of endogenous L1-encoded ORF1 protein (L1ORF1p) levels and translocation of L1ORF1p to HCV assembly sites at lipid droplets. HCV replication interferes with retrotransposition of engineered L1 reporter elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 135 publications
(304 reference statements)
1
17
0
Order By: Relevance
“…The artificial inhibition of stress granule formation increased open reading frame 1 protein (ORF1p), an RNA-binding chaperone encoded by L1 ( Chesnokova et al, 2022 ). This negative role of stress granules on ORF1p was, in the same fashion, observed in the context of hepatitis C virus infection ( Schöbel et al, 2021 ). In tandem with these, this appeared to be the case in cancer cells too.…”
Section: Transposable Elements and Epigeneticssupporting
confidence: 69%
“…The artificial inhibition of stress granule formation increased open reading frame 1 protein (ORF1p), an RNA-binding chaperone encoded by L1 ( Chesnokova et al, 2022 ). This negative role of stress granules on ORF1p was, in the same fashion, observed in the context of hepatitis C virus infection ( Schöbel et al, 2021 ). In tandem with these, this appeared to be the case in cancer cells too.…”
Section: Transposable Elements and Epigeneticssupporting
confidence: 69%
“…L1 activity can also be suppressed by viruses. For example, it has been shown that HIV-1 suppresses L1 retrotransposition by binding to ORF2 using the Vpr protein included in HIV-1 [321] or the hepatitis C virus, which provokes the formation of ORF1 stress granules [322]. Defects in many L1 inhibitory antiviral immune response genes are associated with autoimmune diseases such as Aicardi-Goutières syndrome [323].…”
Section: Antiviral Factorsmentioning
confidence: 99%
“… 30 A recent study also showed that HCV infection results in decreased L1 activity via the redistribution of L1 ORF1p to HCV‐assembly sites in lipid droplets. 49 Further, we recently found that infection with different enteroviruses leads to the suppression of L1 mobility owing to the synergistic effects of diverse viral accessory proteins. 50 Herein, we demonstrated that the newly emerging virus SARS‐CoV‐2 has gained the ability to interfere with L1 activity, which also implies that other coronaviruses have potential L1‐inhibitory features.…”
Section: Discussionmentioning
confidence: 99%